LEKSIKON PERPADIAN PADA BAHASA BEKIDOH DALAM MASYARAKAT DAYAK JUNGUR TONYOK DI KABUPATEN SANGGAU - Cristimorri, Wilhelmus; Syahrani, Agus; Jupitasari, Mellisa (Universitas Tanjungpura, 2025)
This study aims to inventory the lexicon, describe its forms, analyze its lexical meanings, explore its cultural significance, and develop an implementation model for Indonesian language learning based on the rice farming lexicon in the Bekidoh language of the Dayak Jungur community in Sanggau Regency. A descriptive method with a qualitative approach was employed in this research. Data were obtained from Bekidoh language utterances related to the agricultural lexicon in the Dayak Jungur Tonyok community, collected through participant observation, interviews, audio recording, and documentation techniques. The study identified 79 agricultural lexicons in the Bekidoh language, classified into four stages: preplanting (26 lexemes), planting (32 lexemes), harvesting (11 lexemes), and post-harvest (10 lexemes). In terms of linguistic form, 59 lexicons appear as words, further categorized into monomorphemic (53 lexemes) and polymorphemic (6 lexemes). Additionally, 20 lexicons take the form of phrases, classified as endocentric (19 lexemes) and exocentric (1 lexeme). The lexical meanings of all 79 lexicons were analyzed, while cultural meanings were identified in 13 lexicons. Beyond contributing to the documentation of indigenous languages, this study also resulted in the development of an independent curriculum-based teaching module for Grade VII Indonesian language instruction in junior high schools. The findings are expected to serve as a reference for language revitalization efforts and the integration of cultural values into Indonesian language education, particularly in the fields of lexicography and ethnolinguistics.